Epigenetics in a honeybee hive - Cardoso Júnior, Carlos Antônio Mendes (2020)
Epigenetic mechanisms play a major role in gene expression, altering the chromatin structure without changing the DNA sequence. The best studied epigenetic mechanisms are DNA methylation, histone post-translational modifications and non-coding RNAs. This work aimed to explore the functions of these epigenetic mechanisms in the context of several processes in the adult life cycle of the honeybee, Apis mellifera. Firstly, we studied the role of DNA methylation in the longevity of workers and queens. In this context, we determined the effects of social stimuli, such as the queen pheromone and the seasonal demographic variation in the beehive, on the expression of genes that code for enzymes that promote epigenetic alterations on the DNA, RNA and histones. Finally, we investigated how the gene encoding the DNA methyltransferase 3 (DNMT3), a key enzyme for the reprogramming of DNA methylation, is regulated during the major behavioural transition in a worker bee\'s life, namely, the transition from brood care to foraging. Our analyses of Dnmt genes expression and functional assays of their enzymatic activity showed that DNA methylation is associated with longevity in honeybee workers. This likely involves the regulation of vitellogenin, a protein that controls behavioural maturation rates in this caste. Moreover, environmental factors (e.g., queen pheromone and exposure to larvae or young adults) regulate the expression of genes that code for epigenetic modifiers of DNA, RNA and histones. These data suggest that epigenetic reprogramming controls gene expression, allowing adaptation to new social environments. In a second major project we generated methylome data by bisulfite sequencing for comparisons between differentially methylated genes in the brains and ovaries of workers subjected to distinct social contexts. Strikingly, and contrary to expectation, these results revealed only very few changes in DNA methylation in response to a new social context, despite significant alterations in the expression of Dnmt genes. Furthermore, the methylome patterns in ovaries and brains are almost identical, despite the functional differences for these tissues, thus also indicating that DNA methylation is unlikely to regulate honeybee gene expression. This led us to conclude that the DNA methylation machinery possibly displays other functions that are not directly associated with DNA methylation. In line with this hypothesis, in silico analyses and confocal microscopy data showed that a cytoplasmic localization of the DNMT3 protein is predominantly found associated with lipid vesicles. Finally, we found that the honeybee microRNA ame-miR-29b is a bona-fide regulator of Dnmt3 gene expression, and this function is evolutionary conserved between honeybees and mammals, including humans. In conclusion, this study revealed a considerable and unexpected degree of complexity in the roles of epigenetic mechanisms and their regulation of gene expression in a honeybee\'s social life.